Phytochemical contents and diuretic activity of ethanolic extract of the red leaf lettuce (Lactuca Sativa l.) - Lestari, Ratih Guswinda; Amin, Muhammad Saiful; Kusuma, Eka Wisnu (Surya Hijau Manfaat, 2024)
This study was conducted to evaluated of phytochemical content and diuretic activity of the red leaf lettuce. Red leaf lettuce were extracted by cold maceration method using 70% ethanol for the 3 days and remaceration for 1 days. The phytocemical content in ethanolic extract were evaluated by qualitatif method. A total of 25 male rats were divided into 5 groups with CMC Na, a standard drug (furosemide 10 mg/kg), and three different doses (200, 300, and 400 mg/kg) of ethanol extract. Parameters used to determine diuresis activity include first urine latency, urine pH and cumulative urine volume. The ethanolic extract induced diuresis in a dose dependent manner as compared to the negative control. Extracts at doses of 200, 300, and 400 mg/kg produced significant diuresis effects (p<0.05) compared to negative controls with values of diuretic action 1.35; 1.43; and 1.53, respectively. In addition, there was a slightly change in the pH of urine samples of the extract-treated group compared with the negative control. Phytochemicals analysis revealed the presence of alkaloids, flavonoids, phenolics, and tannins.